APLICAÇÃO DOS DIREITOS FUNDAMENTAIS NAS RELAÇÕES PRIVADAS DECIDIDAS PELO ÁRBITRO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
One of the fundamental rights that citizens need to assert is the right to access to justice, a quicker and higher quality procedure. Seeking to resolve the conflict, legislation that expanded the possibility of access to justice through other methods, such as arbitration, which can be carried out by public or private institutions. The results showed that, although the arbitration institute has been an effort to unburden the judiciary and provide greater access to justice, guaranteeing their fundamental rights, even so, this institute has not been able to show the solution to the great existing challenge, of reduce the abyss that exists between the judiciary service and the poorest population, since arbitration has been limited, until the present day, to Private Arbitration Chambers in matters mainly related to business law.